Factors responsible for health inequalities in Nigeria - Bemhemba Iba (Orapuh, Inc., 2023)
Health inequalities are the unjust and avoidable differences in people's health across the population and between specific population groups. These unjust and avoidable differences have remained a major issue in most resource - limited settings and Nigeria is no exception. Where health inequality is in existence, the right to the given population's highest attainable standard of health is not being enjoyed across board. The study seeks to unravel the factors responsible for health inequalities in Nigeria by critically assessing from extant literature the causes of health inequalities using Google search engine, Pubmed/Medline, Google scholar, Microsoft academia and researchgate. The results from the study indicates that the causes of health inequalities in Nigeria are multifactorial however, secioeconomic inequality is a fundamental cause of health inequality. The socioeconomic factors such as poverty, unemployment, illiteracy and place of residence reflect on and affect other components of a health system resulting into poor health outcomes (mortality, morbidity, life expectancy, and general well being). Eradicating health inequality in a country like Nigeria may not be an easy task to achieve however, should adequate steps be taken by the government, private sector and individuals to mitigate it's scourging surge by tackling underlying poverty and unemployment, wealth creation, and enacting policies that will be favourable to all. This will be the most likely way to achieve and sustain health equality in Nigeria.